الصناعات النسيجية في العراق بين الحرفية والتقنيات الحديثة دراسة في جغرافية الصناعات (Journal of the College of Basic Education, 2024)
Industry is considered the mainstay of the Iraqi economy after oil, and it is definitely the mainstay of any successful planned economy. However, in order for Iraq to emerge from its economic depression, which was caused by political tensions in the country throughout its history, it was important that all industrial economic projects be taken care of at all levels, not at the level of the transformational sector. Only, this was the main goal of the research, which was to achieve planning equality at all financial and moral levels for projects related to textile manufacturing in Iraq, without one sector falling behind another.The research presented the historical development of the textile industry in the country from the eighth century until the twentieth century, going through small details about the change in raw materials and the different vision of reality for this important industry. The research also presented a comparison between projects for the craft and manufacturing industries and finding the difference between them. Then the research moved on to study the reality of the textile industry in Baghdad Governorate, specifically in the city and district of Al-Kadhimiya, and statistics representing this display were presented, and then a case was chosen for a government factory in the study area, which is one of the oldest factories that was founded in Al-Irq for the textile industry, which is the cotton factory, and the quantitative method was used to present the factory’s manufacturing efficiency standards; Until we actually understand the problems of this government industry.The last section presented Iraq’s interest in establishing large textile projects, the lack of any evidence about the craft textile industry, and the marginalization of its product, which contributes to the national income with a profit margin that is not taken into account by planning. In conclusion, a number of recommendations were made with the aim of achieving the research objectives in improving craft textile industry projects. Limiting them, having a geographical map for their geographical distribution, and providing adequate support to them will make them more effective than their counterparts in manufacturing factories. In order to contribute to the national income in an open, effective and developmental manner